Assessment of financial costs for the control of bovine trypanosomiasis in Mukono county, Uganda - Laker, C.D.; Mukhebi, A.W.; McDermott, John J.; Patzelt, R.J.; Potsch, C.; Opuda-Asibo, J.; Mehlitz, D. (International Society for Veterinary Epidemiology and Economics, 2000)
Trypanosomosis is an endemic disease in cattle in Mukono District in south eastern Uganda. A multi-disciplinary project was formulated in order to better understand the infection dynamics, and drug sensitivities, of the trypanosome parasites prevalent in Mukono, and also to assess the economic importance of the disease in this pen-urban dairy production system. This paper describes the occurrence, methods and costs of control of bovine trypanosomosis, and its economic importance in dairy cattle in the pen-urban production system of Mukono County. It is hoped that the information generated from this study will help guide policy formulation on the control of bovine trypanosomosis in Mukono in particular, and Uganda in general.